THE EFFECT OF STORE ATMOSPHERE AND PRODUCT PACKAGING ON CONSUMER BUYING BEHAVIOR IN SPORTS STATION MEGA MALL MANADO - Muhammad, Syahbuddin (Sam Ratulangi University, 2016)
The behavioral of consumer depends on a number of factors. In order to keep the consumer there are two ways to approach consumer buying behavior by store atmosphere and consumer buying behavior. This research aims to find the effect of store atmosphere and product packaging on consumer buying behavior in Sports Station Mega Mall Manado. The type of this research is quantitative causal research and the data were gathered from 50 respondents of Sports Station Mega Mall Manado. There are significant effects of store atmosphere and product packaging on consumer buying behavior simultaneously and partially. It is recommended the management of Sports Station Mega Mall Manado should pay intention to indicators of store atmosphere and product packaging to keep their consumers buying behavior.